Surrogacy in India: ethics versus incentive - Kaur, Gurleen; Chawla, Rakesh (International Journal Of Community Medicine And Public Health, 2021)
The word surrogacy has its origin among the Latin term “surrogatus” which suggests a lady acts as a substitute for a pregnant woman. Surrogacy has been in practice form last thirty years. The surrogacy regulated by business can be classified as then, altruistic surrogacy and commercial surrogacy. The paper aim to conduct systematic review on surrogacy. The literature review was conducted using PubMed and alternative search engines. Further, additional information concerning the constitutional articles was collected from search engines like legal service of India, prsinndia.org, icmr.nic.in, Press Information Bureau, Wikipedia, IJCM and Indiankanoon. In India, surrogacy is legally recognised since 2002. This paper looks into various aspects of surrogacy. Factors faced by the surrogate mother such as exploitation, psychological conditions, human rights, dignity and respect, feminism and religious issues are explored. The paper discuss the economic benefit is mostly enjoyed by the medical practitioners. The Indian government tried to curb the problems by updating the law to overcome the challenges but with time government introduce the surrogacy bill in 2016 which addressed many issues and still in 2020 it address various aspects of surrogacy to prevent the exploitation.